The Fire Service for the Removal of a Metallic Penile Constricting Device: A Ready Help When All Else Fail - Olufunmilade A. Omisanjo; Olufemi Ojewuyi; Abimbola Abolarinwa; Oluwaseun Akinola; Mofeyisayo Omorinde; Olabode Oshodi; Stephen Ikuerowo; Ayoade Adedokun; David Oke (Case Reports in Urology)
The placement of a constricting device around the penis is a urologic emergency. Though injuries from constricting penile devices are generally rare, they may be associated with serious complications. There is no standard modality for the removal of penile constricting devices and the management of the patient can therefore prove to be a formidable challenge to the urologist. Timely intervention is always important in preventing complications especially penile gangrene. Depending on the type of device used along with the duration and severity of penile constriction caused, significant resourcefulness may be required in the treatment of the patient. Achieving a timely and successful outcome may require a multidisciplinary approach involving equipment only available with the fire service or other agencies. We report the case of a 30-year-old man with a background psychiatric illness who had his penile constricting device removed under conscious sedation in the emergency room with the aid of a power driven arc saw from the fire service with a successful outcome.